Understanding Vocational School Students’ Work Readiness : The Synergistic Role of Fieldwork Practice and Self-Efficacy - Riyan Yuliyanto; Susilaningsih Susilaningsih; Mintasih Indriayu (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study aims to analyze the synergy between fieldwork practices and self-efficacy in improving the work readiness of vocational school students. This research used a survey method with a quantitative approach. This study involved 1289 populations and 306 samples from three state vocational schools in Surakarta, selected using a proportionate random sampling method. The instruments used in this study consisted of Fieldwork Practice (FWP), Self-efficacy (SE), and Work Readiness (WR) questionnaires. The data obtained were analyzed by statistical testing of descriptive analysis, correlation, and mediation using path analysis. The results of this study revealed that fieldwork practices and self-efficacy contribute significantly to students’ work readiness. The analysis shows that self-efficacy serves as an important mediator in the relationship between fieldwork practices and work readiness, reinforcing the role of practice-based education in preparing students for the world of work. In this study, it was found that the development of education and training programs that focus on improving students’ self-efficacy through fieldwork practices can be a major key in the school-to-work transition.